Rancang Bangun Sistem Miniatur Smart Garden dengan Aplikasi Android Berbasis Internet of Things (IoT) - Alvionita Pingkan; Indira Marasti; Benny Nixon (Spektral, 2023)
Gardening is an activity widely practiced for the preservation of plants or simply as a hobby. However, gardening is still quite challenging for many people due to limited available land. Apart from land constraints, another inhibiting factor is the reliance on manual tasks, such as the watering process. Therefore, one solution that can be implemented is to create a miniature garden with a system that can control and monitor Soil Moisture, temperature, air humidity, and light intensity. The smart garden miniature system utilizes Arduino IDE software, an ESP32 module as the microcontroller, Soil Moisture sensors, DHT-22 sensors, an L298N motor driver to operate the water pump and exhaust fan, and relays connected to LED strips. This system is connected to an Internet of Things-based Android application. The results show that the control and monitoring system operates effectively, in line with the predetermined design.